Salience and Erasure in the Indonesian Government Climate Change Discourse: A Corpus-Based Ecolinguistics Study - Diana Sri Suryani; Suhandano Suhandano (Journal of Language and Literature, 2025)
Climate change is a global phenomenon and has become a challenge to world society. According to that, this study examines linguistics strategies used in the erasure of climate change discourse through ecolinguistics lenses. This study used a specialized corpus that was built through 224 articles from the Ministry of Environment and Forestry (KLHK) website, which was collected with the keywords perubahan iklim ‘climate change’, krisis iklim ‘climate crisis’, and ketahanan iklim ‘climate resilience’. The data was analyzed using Sketch Engine using keywords, concordance, and collocations features. Then, the analysis of data was conducted manually through semantic categorization. This paper used Stibbe’s the void and the mask framework for its analysis. The major themes found in this paper are the government and its activities as a part of international organizations. This paper also found that KLHK used several linguistics strategies to demonstrate climate change, including abstract terms and nominalization to obscure the social actors. Also, the theme of nature, such as non-human species are completely erased from the discourse. These results show that climate change discourse on KLHK’s website is contrary to the ecosophy of ecolinguistics that encourages highlighting the importance of non-human species in such discourse. It is clear that KLHK takes non-human species for granted in their climate change discourse compared to human activity in their discourse.